2008
DOI: 10.1016/j.jfms.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real-time RT-PCR for the quantification of FCoV shedding in the faeces of domestic cats

Abstract: Faecal samples were taken from cats living in multi-cat households with endemic feline coronavirus (FCoV) infection. Total RNA was extracted from faecal suspensions and FCoV RNA was quantified using a real-time reverse transcriptase-polymerase chain reaction (RT-PCR) assay. The real-time RT-PCR threshold cycle (CT) values were consistently high suggesting that the samples contained very little viral RNA. However, experiments in which RNA extracted from FCoV-infected cell culture supernatants was combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 15 publications
2
65
1
Order By: Relevance
“…FCoVs primarily infect enterocytes and spread from the intestine by monocyte-associated viremia (Gunn-Moore et al, 1998;Kipar et al, 2005). They have also been shown to replicate in monocytes/macrophages of healthy cats (Can-Sahna et al, 2007;Dye et al, 2008). Vertical transmission has not been demonstrated (Foley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…FCoVs primarily infect enterocytes and spread from the intestine by monocyte-associated viremia (Gunn-Moore et al, 1998;Kipar et al, 2005). They have also been shown to replicate in monocytes/macrophages of healthy cats (Can-Sahna et al, 2007;Dye et al, 2008). Vertical transmission has not been demonstrated (Foley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Vertical transmission has not been demonstrated (Foley et al, 1997). Persistently infected, asymptomatic carriers spread FCoV since most of these cats shed the virus for a period of months or years, either continuously or transiently (Foley et al, 1997;Cave et al, 2004;Dye et al, 2008;Kipar et al, 2010;Sabshin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleic acids extracted from fecal samples may contain unknown additional molecules, usually referred to as PCR inhibitors, which can interfere with the PCR amplification (Dye et al, 2008;Scipioni et al, 2008;Oikarinen et al, 2009). Presence of PCR inhibitors can lead to false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the surprisingly low copy number of the FCoV sg-mRNA in the gut may be explained with the balanced immune response of the host animals that keeps FCoV replication at low level, and as a consequence, the subgenomic RNA levels may reach much lower rates then their genomic counterparts. Whichever explanation is true, evaluation of quantitative PCR results has to take into consideration the inhibitory compounds of the faecal samples (Dye et al, 2008). The different melting point values of the faecal samples indicating variable number of nucleotide substitutions at the probe-binding site (Rasmussen et al, 2003;Hakhverdyan et al, 2006) revealed at least four different FCoV virus genetic variants in the targeted region of the M gene.…”
Section: Samplementioning
confidence: 99%